0618 Cerebrospinal Fluid Biomarkers in Kleine-Levin syndrome. (27th April 2018) - Ambati, A; Lin, L; Dauvilliers, Y; Mohammed, Q; Huang, Y; Bourgin, P; Arnulf, I; Plazzi, G; Mignot, E
Abstract: Introduction: Kleine-Levin syndrome (KLS) is neurological disorder characterized by recurrent but reversible episodes of hypersomnia, accompanied by behavioral and cognitive abnormalities. Underlying pathophysiology remains unknown and any associated biomarkers have not been described consistently. We employed a high throughput aptamer approach to profile in parallel hundreds of cerebrospinal fluid (CSF) proteins in KLS cases and controls. Methods: A high throughout Aptamer array was used to profile 1123 CSF proteins. CSF from 22 KLS patients (in-episode) and 41 control individuals, matched for age and sex were used in this study. Raw data was normalized to remove any technical artifacts and a z-score transformation was applied. A linear model with an empirical Bayes approach was used to probe differentially expressed proteins in KLS cases and controls. Resulting statistical guarantees were subjected to a 5% FDR control. Results: A set of 26 CSF proteins were identified as differentially expressed in KLS cases versus controls. Among these proteins, KLS cases had significantly higher levels (BH p value<0.005) of IGF-1, IL-34, SPARC, SPARCL1, caspase-10, JAM-B and LY86. Intriguingly, these proteins are tightly linked to monocyte/macrophage innate immune axis. For instance, IGF-1, SPARCL1 and JAM-B drive migration and homing of monocytes/macrophages, IL-34 is vital to survival and proliferation of monocytes, while, SPARC and LY86 promote inflammatory responses associated with macrophages and monocytes. Finally, caspase-10 promotes apoptosis via extrinsic death receptor pathway. Conclusion: KLS cases tended to harbour increased CSF levels of proteins/cytokines implicated in innate immune responses. Support (If Any): KLS Foundation.